2020
DOI: 10.4236/wjet.2020.83026
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Building Information Modelling (BIM) on Engineering Contract Management in Nairobi, Kenya

Abstract: Building Information Modelling (BIM) is a technology and a process that has brought changes in the construction's traditional procurement system. Kenya lacks contractual guidelines on implementation of BIM; this makes the adoption of BIM slow and difficult. Previous research has identified a gap in contractual relationships, roles and resulting risks. The objectives of this study were to investigate BIM adoption in Nairobi and to investigate the influence of BIM on Engineering Contract Management (ECM) in Nair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Simplicity was generated using the average of the variables associated with simplicity while interoperability was generated using the average of variables associated with interoperability. As shown in Figure 4, the results were consistent with studies done by Manza (2016) and Mosse et al (2020). The variables also showed a low performance.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Simplicity was generated using the average of the variables associated with simplicity while interoperability was generated using the average of variables associated with interoperability. As shown in Figure 4, the results were consistent with studies done by Manza (2016) and Mosse et al (2020). The variables also showed a low performance.…”
Section: Discussionsupporting
confidence: 90%
“…Research on issues relating to BIM in Kenya has not been gained sufficient attention from researchers. Mosse et al (2020) found out that usage of BIM in Kenya was low, which is consistent to what Manza (2016) found out in 2016. This study focuses specifically on building contractors, being one of the actors in the construction industry which also include architects, quantity surveyors, civil and structural engineers, service engineers, among others.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…About 1% of respondents repudiated facing problems during BIM implementation. While this represents a minority opinion, it suggests that some organizations may have experienced relatively smooth transitions to BIM-enabled workflows [21]. These organizations may have implemented robust strategies, invested in comprehensive training and support programs, and fostered a culture of innovation and collaboration conducive to successful BIM adoption.…”
Section: Identification and Mitigation Of Cost-related Risksmentioning
confidence: 97%
“…[20] asserts that the ramifications of BIM transcend software and incorporate workflow, project delivery, and management practices. Notwithstanding its inherent capabilities, obstacles continue to persevere, as delineated by [21], who pinpoint knowledge deficiencies and compliance concerns as hindrances to the implementation of BIM. The findings of this study underscore the significance of formulating comprehensive strategies to surmount the barriers hindering the effective implementation of BIM in civil engineering projects, particularly in regions like Nairobi.…”
Section: Literature Reviewmentioning
confidence: 99%